El problema de la deuda externa en África - Fernández Ruiz, Jorge (El Colegio de México, 2008)
Since the 1980s many African countries began to experience profound limitations to pay their foreign debt. This scenario has led some authors to argue that elevated levels of foreign debt constitute a formidable obstacle to increase the overall well being of the respective African nations. This article examines the root causes of these increased levels of debt, as well as the various mechanisms which it has confronted. It concludes with an overview of the available evidence regarding the consequences of high levels of foreign debt and the benefits that are emerging as a result of their reduction.